Quanzhen Daoists in Chinese society and culture, 1500 - 2010 - Liu, Xun; Goossaert, Vincent (China research monograph, 2013)
"By combining text-based and fieldwork-based approaches, this volume provides a fuller and more complex picture of the place of Quanzhen Daoism in Chinese society and culture as it has fared in the heady political, social, and cultural transformations of modern China"--